The Construction of Feminine Discourse in the Context of Negotiated Patriarchy in the Religious Series "Para Pencari Tuhan 2025" - Kinamin Mutiara Bilkis; Muhammad Hambali (JENTERA: Jurnal Kajian Sastra, 2026)
This study aims to analyze the discourse construction of femininity within negotiative patriarchal relations in the digital religious series Para Pencari Tuhan 2025. The study is motivated by the limited research on the representation of women in digital religious series, particularly studies examining the relationship between religious values, patriarchal culture, and the construction of femininity through a critical discourse analysis approach. This research employs a qualitative descriptive method using Teun A. Van Dijk’s critical discourse analysis model. The data consist of all episodes of Para Pencari Tuhan 2025 streamed on the Vidio platform, with data sources including dialogues, narratives, characterizations, and scenes representing femininity. Data were collected through documentation, observation, note-taking, and screenshot techniques and analyzed through the dimensions of text structure, social cognition, and social context. The findings reveal that femininity is constructed through the representation of women as domestic, emotional, and moral supporters of the family, legitimized by religious narratives. In the dimension of social cognition, patriarchal values are internalized in ways that position women in subordinate roles. Meanwhile, the social context dimension reveals a pattern of negotiative patriarchy, in which women are allowed to participate in the public sphere while remaining responsible for domestic roles in accordance with religious values and patriarchal norms. These findings indicate that digital religious series not only represent social reality but also reproduce and negotiate the construction of femininity within contemporary society. Abstrak Penelitian ini bertujuan menganalisis konstruksi wacana feminitas dalam relasi patriarki negosiatif pada serial religi digital “Para Pencari Tuhan 2025”. Penelitian ini dilatarbelakangi oleh masih terbatasnya kajian mengenai representasi perempuan dalam serial religi digital, khususnya yang mengkaji keterkaitan antara nilai religius, budaya patriarki, dan konstruksi feminitas melalui pendekatan analisis wacana kritis. Penelitian menggunakan metode deskriptif kualitatif dengan pendekatan analisis wacana kritis model Teun A. van Dijk. Data penelitian berupa seluruh episode “Para Pencari Tuhan 2025” yang ditayangkan melalui platform Vidio dengan sumber data berupa dialog, narasi, penokohan, dan adegan yang merepresentasikan feminitas. Data dikumpulkan melalui teknik dokumentasi, simak, catat, dan tangkapan layar, kemudian dianalisis melalui dimensi struktur teks, kognisi sosial, dan konteks sosial. Hasil penelitian menunjukkan bahwa feminitas dikonstruksikan melalui representasi perempuan sebagai sosok domestik, emosional, dan pendukung moral keluarga yang dilegitimasi oleh narasi religius. Pada dimensi kognisi sosial, ditemukan internalisasi nilai patriarki yang menempatkan perempuan dalam posisi subordinat. Sementara itu, pada dimensi konteks sosial ditemukan pola patriarki negosiatif yang memperlihatkan perempuan dapat berpartisipasi dalam ruang publik, tetapi tetap dituntut untuk menjalankan peran domestik sesuai nilai religius dan budaya patriarki. Temuan ini menunjukkan bahwa serial religi digital tidak hanya merepresentasikan realitas sosial, tetapi juga mereproduksi dan menegosiasikan konstruksi feminitas dalam masyarakat kontemporer.